Non-cognate ligands of hepatitis C virus envelope broadly neutralizing antibodies induce virus-neutralizing sera in mice - Walimbwa, Stephen Ian; Bharadwaj, Shiv; Kosztyu, Petr; Vankova, Lucie; Kuchar, Milan; Kopecna, Eliska; Effenberg, Roman; Drasar, Lukas; Raskova Kafkova, Leona; Maly, Petr; Raska, Milan (Frontiers in Immunology, 2025)
IntroductionThe persistent rise in new Hepatitis C virus (HCV) infections threatens WHO efforts to eliminate HCV infection by 2030. Although direct-acting antiviral (DAA) drugs are efficacious, access remains limited, reinfections occur, and perinatal infections continue to pose long-term complications. Therefore, an effective anti-HCV vaccine is urgently needed.MethodsWe employed a highly complex combinatorial Myomedin-loop scaffold library to identify variants binding to paratopes of HCV E2-specific broadly neutralizing antibodies (bNAbs) HC-1AM and HC84.26.WH.5DL. The selected binders, named SHB and WIN, respectively, represent non-cognate mimotopes of the aforementioned bNAbs. These binders were subsequently used as immunogens in experimental mice to elicit serum antibodies capable of binding to HCV E2 and neutralize HCV pseudotyped viruses.Results and discussionThe non-cognate mimotopes SHB and WIN competed with the E2 glycoprotein for bNAbs binding and, after immunizing experimental mice, elicited E2- and HCV-pseudovirus-specific antibodies. WIN- and SHB-immunized mice exhibited neutralization against 15 HCV pseudoviruses with varying neutralization sensitivities. The most potent binders WIN028 and WIN047, were modified with a C-terminal His-tag, allowing the generation of WIN proteoliposome and subsequent use in experimental mice immunizations. Hyperimmune sera exhibited improved binding to HCV E2 and neutralized 60% of the tested HCV pseudoviruses. The broad neutralization of HCV pseudoviruses achieved by hypperimmune sera from SHB- and WIN-immunized mice highlights the potential of this approach in the HCV vaccine design.